'Just Right' job design: A conceptual framework for sustainable work in rail driving using the Goldilocks Work Paradigm. (November 2022) - Naweed, Anjum; Chapman, Janine; Vandelanotte, Corneel; Chappel, Stephanie E.; Holtermann, Andreas; Straker, Leon
Abstract: Excessive physical demand at work has traditionally been connected with adverse health outcomes, but excessive sitting is now also being recognised as an occupational hazard and emerging work-related risk. Traditional preventive occupational health and ergonomics programs are useful but limited through reliance on individual behaviour change and time-diversion from productive work. A new 'Goldilocks Work Paradigm' aims to optimise health and productivity by using movements of productive tasks. Using rail driving as a specific case of a highly sedentary and inflexible working environment, we construct a conceptual framework for designing better jobs, arguing that a theoretical amalgamation of the new Goldilocks Work Paradigm with System Thinking, Participatory Ergonomics, and a Risk Management Framework, is needed, for establishing a unified, strategic approach—a 'just right' job design model. We extend this by outlining a practical process of designing better jobs with tools that can be used to achieve it. Highlights: Systems thinking explains a gradual drift into sedentariness in rail driving work. The Goldilocks Work Paradigm is applied to this highly sedentary work environment. Hierarchical task analysis of train operations identifies opportunity for movement. A common conceptual framework is constructed to support sustainable work. A 'just right' job design model is presented for practical implementation.